Effect of operational variables on biological hydrogen production from palm oil mill effluent by dark fermentation using response surface methodology - Akhbari, Azam; Zinatizadeh, Ali Akbar; Vafaeifard, Mohsen; Mohammadi, Parviz; Zainal, Bidattul Syirat; Ibrahim, Shaliza (Desalination Publications, 2019)
This work is a study of the performance and effect of operational parameters on biohydrogen production from palm oil mill effluent by dark fermentation in batch mode. The tests were conducted with samples prepared in 150 mL bottles using a shaker at 150 rpm. Response surface methodology was applied to investigate the influence of the four significant independent parameters viz. pH (5, 5.5, and 6), temperature (30°C, 35°C, and 40°C), substrate concentration (5,000, 12,500, and 20,000 mg L –1 ) and inoculum–substrate ratios of 2, 0.8, and 0.5 (expressed as volatile suspended solid (VSS) basis) with the inoculum concentration of 10 g L –1 VSS on biohydrogen production. All the experiments were analyzed at the incubation time of 8, 16, and 24 h. Upon seeing each interval, the results were compared. The highest chemical oxygen demand (COD) removal, the hydrogen content in the biogas as hydrogen percentage (H 2 %), and hydrogen yield (HY) were obtained 58.3%, 80%, and 3.63 mol H 2 mol –1 glucose, respectively, at 24 h incubation time. An overlay study was done to find an overall optimization of the parameters. The optimized conditions were COD removal 49%, HY 3.2 mol H 2 mol –1 glucose, and hydrogen percentage 80%. Also, the Monod model was studied to calculate the kinetics constants of the maximum substrate utilization rate (U max ) and half-velocity K s which are found to be 0.261 g L –1 d –1 and 0.349 mg L –1 , respectively. © 2019 Desalination Publications. All rights reserved.